Implementasi Alimentasi Anak Dalam Suatu Perceraian (Studi Kasus Putusan Pengadilan Agama Ambon Nomor: 312/Pdt.G/2018/Pa Ambon - Anggitta Meirina Lubis; La Ode Angga; Muchtar Anshary Hamid Labetubun (Faculty of Law Pattimura University, 2021)
Introduction: The obligations of the father and mother to care for and provide for the child still continues even though the marriage of the two partners has been divorced. According to Article 105 KHI based on marriage law in Indonesia, judges have the right to appoint the mother as the holder of child custody if the child is under 12 years of age / is not yet mumayyiz, and the father is the bearer of the child's life expenses. However, in practice the contents of the verdicts are often ignored, often the fulfillment of children's livelihoods is not carried out by fathers.Purposes of the Research: Knowing and analyzing the implementation of Child Alimentation (Case Study of Ambon Religious Court Decision Number: 312 / Pdt.G / 2018 / PA. Ab).Methods of the Research: This research method is empirical juridical research. The source of legal materials used is primary, secondary and tertiary legal materials. Data collection techniques through interviews and documentation. Data processing techniques obtained from the results of interviews and then in processing the data the author clarifies with the aim of obtaining an overview of the answers. Data analysis using qualitative methods.Results of the Research: Providing support for a child will continue to be the responsibility of a father until the child is an adult. as contained in Presidential Instruction Number 1 of 1991 concerning Compilation of Islamic Law (KHI) and Law Number 1 of 1974 concerning marriage, there are several factors inhibiting the implementation of the alimentation. The factors of non-implementation of alimentation include economic, social factors in society, and the existence of a legal vacuum against the implementation of decisions related to sanctions and the executive power of living hadhanah, Ambon Religious Court.